Prediction of surface roughness in hard milling of AISI D2 tool steel - Lajis, M. A.; Karim, A.N. Mustafizul; Amin, A. K. M. Nurul; Hafiz, A.M. Khalid (2007)
This paper presents a study of the development of a surface roughness model in end milling of hardened steel AISI D2 using PVD TiAIN coated carbide cutting tool. The hardness of AISI D2 tool lies within the range of 56-58 HRe. The independent variables or the primary machining parameters selected for this experiment were the cutting speed, feed, and depth of cut. First and second order models were developed using Response Surface Methodology (RSM). Experiments were conducted within specified ranges of the parameters. Design-Expert 6.0 software was used to develop the surface roughness equations as the predictive models. Analysis of variance (ANOVA) with 95% confidence interval has indicated that the models are valid in predicting the surface roughness of the part machined under specified condition.